Managing Depression, Anxiety, and Stress: Nursing Approaches - Dr. S. P. Subashini (Innovational: Journal of Nursing and Healthcare, 2025)
Depression, anxiety, and stress are prevalent psychological conditions in healthcare settings, affecting both patients and nurses. These interrelated yet distinct mental health challenges significantly impact patient outcomes, treatment adherence, and the overall quality of care. Nurses play a vital role in early identification, assessment, and management of these conditions through evidence-based practices and therapeutic communication. This review explores the signs, symptoms, and etiological factors of depression, anxiety, and stress, emphasizing the importance of screening tools such as PHQ-9, GAD-7, and DASS-21. It highlights nursing interventions across psychological, pharmacological, lifestyle, and holistic domains, including Cognitive Behavioral Therapy (CBT) techniques, mindfulness practices, emotional support, and patient education. Challenges such as stigma, resource limitations, and burnout are addressed, along with recommendations for enhancing nurse training, integrating mental health care into general practice, and promoting policy support. The review reaffirms the nurse's critical role in providing comprehensive, compassionate, and effective mental health care.